2022
DOI: 10.1101/2022.03.01.22271582
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Duration of viable virus shedding in SARS-CoV-2 omicron variant infection

Abstract: Clinical features of SARS-CoV-2 Omicron variant infection, including incubation period and transmission rates, distinguish this variant from preceding variants. However, whether the duration of shedding of viable virus differs between omicron and previous variants is not well understood. To characterize how variant and vaccination status impact shedding of viable virus, we serially sampled symptomatic outpatients newly diagnosed with COVID-19. Anterior nasal swabs were tested for viral load, sequencing, and vi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 9 publications
5
59
0
Order By: Relevance
“…This is consistent with previous data showing no major differences in Omicron infection duration when compared to Delta 16 or time to culture or PCR conversion between the two variants. 15 Similar to the findings of Boucau et al 15 , we found no significant difference in culture or PCR conversion in boosted participants when compared to those who were fully vaccinated. This suggests that the population level protection provided by COVID-19 booster vaccination doses against Omicron 17,18 result from protection against infection rather than altered viral kinetics in vaccinated individuals causing reduced transmission or more rapid clearance.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is consistent with previous data showing no major differences in Omicron infection duration when compared to Delta 16 or time to culture or PCR conversion between the two variants. 15 Similar to the findings of Boucau et al 15 , we found no significant difference in culture or PCR conversion in boosted participants when compared to those who were fully vaccinated. This suggests that the population level protection provided by COVID-19 booster vaccination doses against Omicron 17,18 result from protection against infection rather than altered viral kinetics in vaccinated individuals causing reduced transmission or more rapid clearance.…”
Section: Discussionsupporting
confidence: 89%
“…14 Our results are similar to data from the National Basketball Association cohort which found 40% with cycle thresholds of less than 30 at day 5, though this study did not examine culture positivity. 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly time to negativity or time to reaching a lower viral load (Ct>30) were very similar, when comparing data from the phases in the pandemic when alpha, delta or omicron were dominant. Previous data comparing the time to negative PCR in patients infected with omicron versus delta variant indicated also that there is no significant difference between the two groups 10 .…”
Section: Discussionmentioning
confidence: 94%
“…The POSITIVES cohort is a longitudinal study of individuals with COVID-19 infection that aims to characterize virologic and immunologic aspects of infection [4][5][6]. To better understand the clinical phenomenon of symptom relapse after nirmatrelvir-ritonavir treatment, we selectively enrolled seven ambulatory individuals recently treated with nirmatrelvir-ritonavir with recurrent symptoms after initial resolution.…”
Section: Study Participantsmentioning
confidence: 99%